2007
DOI: 10.1002/icd.530
|View full text |Cite
|
Sign up to set email alerts
|

Development of chromatic induction in infancy

Abstract: The perception of colour in an embedded field is affected by the surround colour. This phenomenon is known as chromatic induction. In the present study we investigated whether the colour perception by infants aged 5-7 months could be affected by the surround colour. In Experiments 1 and 2 each stimulus was composed of an array of six squares in tandem. The colour appearance of the array in the familiarization stimulus was established by chromatic induction. In Experiment 1 we used familiarization stimuli that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…However, the difference was not significant (w 2 2X43, ns). Also, the proportions of excluded participants were similar to those in previously reported habituation experiments with infants [eg Arterberry and Yonas (1988), 62.5%; Arterberry and Yonas (2000), 54.5%; Okamura et al (2007) experiment 1A, 41.8%; experiment 1B, 27.27%; experiment 2A, 33.3%; experiment 2B, 34.7%].…”
Section: Discussionsupporting
confidence: 83%
“…However, the difference was not significant (w 2 2X43, ns). Also, the proportions of excluded participants were similar to those in previously reported habituation experiments with infants [eg Arterberry and Yonas (1988), 62.5%; Arterberry and Yonas (2000), 54.5%; Okamura et al (2007) experiment 1A, 41.8%; experiment 1B, 27.27%; experiment 2A, 33.3%; experiment 2B, 34.7%].…”
Section: Discussionsupporting
confidence: 83%
“…In another recent study, the impact of environmental or surround color on color perception was investigated. The researchers found that color perception of 7-month-old infants was affected by environmental color (Okamura et al 2007). These studies shed light on the importance of color as a visual design element in children's environments.…”
Section: Introductionmentioning
confidence: 97%
“…These results suggest that infants have trichromatic color vision by at least 4 months of age. Because of the development of low-level sensitivity to chromatic information as summarized above, most of the studies on infant color perception and cognition have examined infants over 5 months of age (e.g., Okamura, Kanazawa, & Yamaguchi, 2007). Considering this and the learning abilities during infancy as suggested by Reardon and Bushnell (1988), we hypothesized that the association between daily objects and their canonical colors emerges between 5 and 7 months of age.…”
Section: Introductionmentioning
confidence: 97%